Usability Assessment of the KAIA-PAY Application Using Nielsen's Usability Attributes Model - Deni Saepulloh Deni; Sribekti Handayani Ningsih (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2026)
Web browser applications such as KAIA-PAY have become a major requirement in the digitalera for credit agent users. KAIA-PAY facilitates users in serving credit purchases and gettinginformation easily. Although many users were satisfied with the app's performance, some usersalso expressed their dissatisfaction. Therefore, this study aims to evaluate usability using theNielsen Usability Model in the KAIA-PAY application to assess user satisfaction and identifyexisting usability problems. Evaluation includes aspects of ease of learning (learnability),efficiency (efficiency), user's ability to remember (memorability), error rate (errors), usersatisfaction (satisfaction), usability (usability), conformity to specifications (Conformity toSpecification), and Responsiveness (Responsiveness). The collected data was analyzed usingthe Smart PLS 4 application to understand the level of usability of the KAIA-PAY applicationand the factors that influence it. The results of the study found that KAIA-PAY wassignificantly influenced by the Learnability and Satisfaction variables.